DESTRUCTION OF THE POPULATION AND MURDER AS CRIME AGAINST HUMANITY (International relations and international law Journal, 2016)
As crimes against humanity, murder and extermination of population have specific features. Although these crimes seem similar prima facie, they are different in relation to their components. The component of murder considers that an action fulfilled in the form of any government policy or plan is aimed at anyone, not against a person or persons concretely. Extermination is the destruction, in whole or in part, of the or a (depending on the specifity of popluation) population, and physical destruction through physical and biological means. Both aforementioned crimes were addressed in the Charter ofthe Tokyo Tribunal, the principle VI of the Nuremberg Principles, the charters of the tribunals for Yugoslavia and Rwanda, the Code of Crimes against the Peace and Security ofMankind, and the Statute of the International Criminal Court.
Keywords: destruction of the population; murder; crime against humanity